Perlantikan wanita sebagai hakim syariah di negeri Kedah - Abu Bakar, Md Zawawi; Akmal Ismail, Nur Syakiran; Mohd Noor, Asmah Bee (Sekolah Pembangunan Sosial, 2007)
Decision makers pay more attention to some issues to develop a policy. Problem must be recognized before a policy can be made. This paper discusses the issues of woman as a judge at Syariah Court. In analyzing this issue the study explores the perception of oficers at Syariah Court and Jabatan Agama lslam Negeri Kedah regarding the issues. The finding shows that there is no differences in perceptions regarding the issue between oficers at Syariah Court and ofJicers at Jabatan Agama Islam. Therefore this study concluded that the issue must be discussedfurther ifthe government to make a new policy in appointing woman as a judge in the Syariah Court.